2016
DOI: 10.1016/j.jos.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of diffuse idiopathic skeletal hyperostosis in Japan – the first report of measurement by CT and review of the literature

Abstract: The prevalence of DISH based on CT was 27.1%, which was higher than that of x-ray. In addition, intra- and inter-observer error by review of CT was less than that of x-ray. CT evaluation would be a better method for precise understanding of the state of DISH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
71
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 16 publications
6
71
1
1
Order By: Relevance
“…10,[15][16][17][18] In recent years, the accuracy in diagnosis of this disease has been improved by the use of CT instead of radiography, resulting in an approximately 25% increase in the number of DISH cases reported. [10][11][12][13][14][15][16][17][18] The prevalence of DISH increases with advanced age and is associated with sex (male) and complications caused by diabetes mellitus or obesity. [19][20][21][22] However, there are many unresolved questions about the pathophysiology of DISH, and it is unknown how quickly ossification progresses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,[15][16][17][18] In recent years, the accuracy in diagnosis of this disease has been improved by the use of CT instead of radiography, resulting in an approximately 25% increase in the number of DISH cases reported. [10][11][12][13][14][15][16][17][18] The prevalence of DISH increases with advanced age and is associated with sex (male) and complications caused by diabetes mellitus or obesity. [19][20][21][22] However, there are many unresolved questions about the pathophysiology of DISH, and it is unknown how quickly ossification progresses.…”
Section: Discussionmentioning
confidence: 99%
“…These results are comparable to the findings in a previous report. 10 Mata et al 28 scored ligament ossification using anteroposterior and lateral radiographs of the cervical, thoracic, and lumbar spinal column; lateral views of both malleoli, heels, and elbows; and anteroposterior views of the pelvis and shoulder in 55 patients with DISH and 35 patients with spondylosis, assigning a score of 0 to cases with no ossification, a score of 1 to cases with ligament ossification but without bridging, a score of 2 to cases with incomplete bridging, and score of 3 to cases with complete ossification (Table 1). They reported that scoring would enable quantitative analysis of the relationship of changes in ligament ossification and diagnostic imaging findings to the clinical features.…”
Section: Discussionmentioning
confidence: 99%
“…Indications for surgical intervention are a lack of improvement after conservative treatment, symptoms intensification with weight loss, as well as the appearance of "red flags" or extraesophageal symptoms (dysphonia, aspiration pneumonia, dyspnea, etc.) [2,21,22,23]. In extreme cases, patients are unable to consume solid food, only semi-solid or liquid.…”
Section: Discussionmentioning
confidence: 99%
“…1 The prevalence of DISH is reported to be as high as 27.1%, increasing with age and demonstrating a male preponderance of up to 6:1. 2,3 DISH affecting the cervical vertebrae can be referred to as anterolateral cervical hyperostosis (ACH). ACH is seen in up to 78% of DISH cases 1 and is associated with clinical symptoms including: reduced range of movement, dysphagia, dysphonia and dyspnoea.…”
Section: Introductionmentioning
confidence: 99%